Lipase mediated separation of triterpene structural isomers, alpha- and beta-amyrin - Haldar, Saikat; Kale, Balaji S.; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
Pentacyclic triterpenoids alpha- and beta-amyrin possess a wide range of biological and pharmacological activities. High structural similarity between these two structural isomers makes their chromatographic separation an ineffective and tedious choice. In this study, Candida rugosa lipase catalyzed separation protocol for the isolation of individual isomers has been developed. In the presence of vinyl acetate as the acyl donor, Candida rugosa lipase carried out acetylation of beta-amyrin more efficiently as compared to alpha-amyrin leading to a kinetic separation. The conditions of transesterification reaction were optimized systematically, which was utilized to separate alpha- and beta-amyrin from a mixture obtained from the latex of Plumeria obtusa. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Amyrin; Candida rugosa; Kinetic separation; Lipase; Structural isomer

Lipase catalyzed synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh; Paul, Ajay; Mulani, Fayaj Alam; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Data in Brief, 2018)
In this data article we describe screening of various lipases for the regioselective acylation of Andrographolide. Each lipase was screened with seven acyl donors. Amano lipase AK from Pseudomonas fluorescens was used for the synthesis of two new acylated andrographolide derivatives. Two new compounds, andrographolide-14-propionate and andrographolide-14-caproate were characterized by various spectral studies. These two derivatives showed more antimicrobial activity than andrographolide.

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis (vol 184, 112669, 2021) - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, Hirekodathakallu V. (Phytochemistry, 2021)